Guide to the WTO and GATT Economics, Law and Politics - Koul, Autar Krishen (Springer Singapore, 2018)
This book analyzes how today's system of international trade law and international economic relations has evolved over the last six decades. Focusing on the major innovations that came with the inception of the World Trade Organization (WTO) with its various agreements in 1994, it also provides in-depth commentary on the intense debate over important matters that remain unsettled. Topics covered include the WTO dispute settlement mechanism; the General Agreement on Trade in Services (OATS); the Agreement on Trade-Related Investment Measures (TRIMS); intellectual property rights - the Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS); areas still covered by the General Agreement on Tariffs and Trade (GATT) 1947; the Most Favoured Nation (MFN) concept; special provisions relating to agriculture and textiles; sanitary and phytosanitary measures; technical barriers to trade; pre-shipment inspection; and import licensing procedures. The book would be an excellent resource for scholars as well as practitioners working in the field of international arbitration and trade laws.